Vietnam’s Proactive International Integration: Case Studies in Defence Cooperation - Thayer, Carlyle A. (VNU Journal of Science: Social Sciences and Humanities; Vol 32 No 1S, 2016)
In January 2016, Vietnam’s Cabinet approved the Overall Strategy for International Integration up to 2020, Vision to 2030 (Chiến lược tổng thể hội nhập quốc tế đến năm 2020, tầm nhìn 2030). This document reviewed Vietnam’s bilateral strategic and comprehensive partnerships with twenty-five countries and concluded that more efforts had to be made to implement political commitments and to deepen cooperation, including defence and security cooperation. This paper focuses on Vietnam’s efforts in 2016 to step up international defence cooperation with major strategic partners including the five permanent members of the United Nations Security Council (China, France, Russia, the United Kingdom and the United States) as well as India and Japan. This paper discusses the exchange of high-level visits, strategic dialogues, defence cooperation agreements (equipment procurement, military technology, education and training, military medicine and maritime security), naval port visits and engagement activities, and national defence industry cooperation. This paper concludes that Vietnam seeks to use international defence cooperation to give each strategic partner equity in Vietnam’s stability and development in order to ensure Vietnam’s non-alignment and strategic autonomy.